2004
DOI: 10.1203/01.pdr.0000142587.59238.bd
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Neonates: Relationship Between Measured and Derived Anthropometry with Dual-Energy X-Ray Absorptiometry Measurements

Abstract: This study examined the relationship between measured and derived anthropometric measurements with dual-energy x-ray absorptiometry measured lean and fat mass at 3.0 Ϯ 2.8 (SD) days in 120 neonates with birth weights appropriate (AGA; n ϭ 74), large (LGA; n ϭ 30); or small (SGA, n ϭ 16) for gestational age. Anthropometric measurements, including total body weight and length, and regional measurements, including circumferences of head, chest, abdomen, midarm, and midthigh and dynamic skinfold thickness (15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 33 publications
6
62
2
Order By: Relevance
“…This also suggests that the 'thin-fat' paradigm may not apply to the SGA and AGA babies in this group, although the indication (because of the relatively small numbers) is that it may apply to LGA babies. AFI is analogous to percentage body fat and, in studies where both parameters were measured 10 , a comparison of the relationship of AFI or percentage body fat with mean birth weight across gestational groups showed that both increase significantly. Neonatal body composition could track into childhood and adulthood.…”
Section: Discussionmentioning
confidence: 98%
“…This also suggests that the 'thin-fat' paradigm may not apply to the SGA and AGA babies in this group, although the indication (because of the relatively small numbers) is that it may apply to LGA babies. AFI is analogous to percentage body fat and, in studies where both parameters were measured 10 , a comparison of the relationship of AFI or percentage body fat with mean birth weight across gestational groups showed that both increase significantly. Neonatal body composition could track into childhood and adulthood.…”
Section: Discussionmentioning
confidence: 98%
“…Despite a flurry of investigations that used ADP to characterize patterns of fat and lean mass gain during infancy (12)(13)(14), few studies, to our knowledge, have formally assessed the relation between derived anthropometric indexes and directly measured body composition. So far, only a few small cross-sectional analyses of data from both term and preterm infants reported poor correlations of birth weight, as well as weight-and length-based indexes, with neonatal FM (15)(16)(17). To our knowledge, no study to date has evaluated whether or how changes in derived indexes correlate with changes in body composition during infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows that this disproportion occurs in many macrosomic as well as normal-weight babies, whether or not their mother had glucose intolerance. Macrosomic neonates usually have a head and chest of equal size [15,16], or have a head substantially smaller than the chest [16], the opposite of what is observed in most normal birth weight babies [2,3]. Our sample size was inadequate to assess the difference in the frequency of Erb palsy, or even shoulder dystocia between cases and controls, because the prevalence of both is low (about 20/1000 for shoulder dystocia and 2.5/1000 for brachial plexus injury).…”
Section: Discussionmentioning
confidence: 99%